How to write a thesis - Murray, Rowena (Maidenhead, Berkshire, Eng. Open University Press, 2011)
Providing down-to-earth guidance to help students shape their theses, the author offers valuable advice and practical tips and techniques. Useful summaries and checklists help students to stay on track or regain their way. Moving beyond the basics of thesis writing, the book introduces practical writing techniques such as freewriting, generative writing and binge writing. Issues such as working out the criteria for your thesis, writer's block, writing a literature review and making notes into a draft are also covered. -- Back cover.
Introduction : how to write 1,000 words an hour -- Thinking about writing a thesis -- Starting to write -- Seeking structure -- The first milestone -- Becoming a serial writer -- Creating closure -- Fear and loathing : revising -- It is never too late to start -- The last 385 yards -- After the thesis examination : more writing?
Keywords: Dissertations, Academic -- Authorship; Report writing; Academic writing